1998
DOI: 10.1086/301782
|View full text |Cite
|
Sign up to set email alerts
|

DAX1 Mutations Map to Putative Structural Domains in a Deduced Three-Dimensional Model

Abstract: The DAX1 protein is an orphan nuclear hormone receptor based on sequence similarity in the putative ligand-binding domain (LBD). DAX1 mutations result in X-linked adrenal hypoplasia congenita (AHC). Our objective was to identify DAX1 mutations in a series of families, to determine the types of mutations resulting in AHC and to locate single-amino-acid changes in a DAX1 structural model. The 14 new mutations identified among our 17 families with AHC brought the total number of families with AHC to 48 and the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
1
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 46 publications
4
70
1
1
Order By: Relevance
“…Previous reports have suggested that the majority of missense mutations are concentrated in the LDB-like region (Phelan and McCabe, 2001;Zhang, et al, 1998). However, this report provides further evidence that there is no existence of mutational hotspots concerning frameshift and nonsense mutations in the NR0B1 gene.…”
Section: Resultscontrasting
confidence: 48%
See 1 more Smart Citation
“…Previous reports have suggested that the majority of missense mutations are concentrated in the LDB-like region (Phelan and McCabe, 2001;Zhang, et al, 1998). However, this report provides further evidence that there is no existence of mutational hotspots concerning frameshift and nonsense mutations in the NR0B1 gene.…”
Section: Resultscontrasting
confidence: 48%
“…This observation is consistent with the overall distribution of NR0B1 mutations (Phelan and McCabe, 2001) and thus explains that the majority of the novel mutations reported are frameshift mutations. The occurrence of the 734_740del mutation in two unrelated families is a rare phenomenon, while only a few other mutations have been reported to occur in unrelated families (c.501del (Zhang, et al, 2001), c.1292del (Guo, et al, 1995;Zhang, et al, 1998)). The frameshift and nonsense mutations were detected throughout the entire NR0B1 coding region (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3A; A of the ATG start codon designated ϩ1; 501delA of IV-2 previously reported (22)]. This single nucleotide deletion results in a frame shift and premature stop codon at position 263.…”
Section: Mutation Analysis Of the Dax1 Genementioning
confidence: 87%
“…The gel is stained and a scanned image of the gel is obtained. Two images from a control and a test sample or samples stimulated under two different environmental conditions are obtained and compared for differences in protein expression or protein modification [6,7]. An example is provided in Fig.…”
Section: General Optical Image Technologiesmentioning
confidence: 99%